Gifted Students’ Beliefs about Knowledge and Learning - Oğuzhan Nacaroğlu; Oktay Kızkapan (Journal of Science Learning, 2021)
Epistemological beliefs can be defined shortly as beliefs about the source, certainty, organization of knowledge, and beliefs on ability and speed of learning. Word association tests (WAT) are practical alternative assessment and evaluation tools that can reveal students' thoughts on different concepts. In this regard, this research aims to investigate the gifted students' beliefs about "knowledge" and "learning" concepts by using WAT. Phenomenology design was utilized in the research. The study was carried out with 118 gifted students studying at Science and Art Center in Turkey's Central East Anatolia Region in the 2018-2019 academic year. The word association test was used as a data collection tool. In this context, participants were given the concepts "knowledge" and "learning" and asked to write their associations about these concepts. They were then asked to make a sentence about each concept. Deductive content analysis was used to analyze the data. The research findings revealed that most students have sophisticated epistemological beliefs in specific knowledge, simple knowledge, source of knowledge, and quick learning dimensions. However, it has been found that the number of students in the sophisticated and naive categories of innate ability dimension is approximately equal.